2018
DOI: 10.1039/c8an01736k
|View full text |Cite
|
Sign up to set email alerts
|

Solvent directed selective and sensitive fluorescence detection of target ions using a coumarin–pyridine probe

Abstract: The solvatochromic properties of a coumarin–pyridine probe were utilized as a cheap and effective way for designing fluorescent probes for Mg2+ and PPi with high selectivity and nanomolar level sensitivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…During the investigation on coumarin-based fluorescent sensors, our group found that the metal complex of a very simple coumarin could exhibit interesting fluorescence properties and be developed as a fluorescent sensor for metal ions or anions. , In the structures of D1 and D2 , the carboxyl group was designed as a metal chelation site, which enabled their ability to coordinate with metal ions. During the investigation of the optical response of D1 and D2 toward various metal ions, we found that the most significant fluorescence quenching was observed when Cu 2+ was added (Figure S7).…”
Section: Resultsmentioning
confidence: 99%
“…During the investigation on coumarin-based fluorescent sensors, our group found that the metal complex of a very simple coumarin could exhibit interesting fluorescence properties and be developed as a fluorescent sensor for metal ions or anions. , In the structures of D1 and D2 , the carboxyl group was designed as a metal chelation site, which enabled their ability to coordinate with metal ions. During the investigation of the optical response of D1 and D2 toward various metal ions, we found that the most significant fluorescence quenching was observed when Cu 2+ was added (Figure S7).…”
Section: Resultsmentioning
confidence: 99%
“…The construction of coordination-based coumarin fluorescent probes for detecting metal ions is a highly topical research field because of their ease of modification, relatively high-fluorescence quantum yield, and molar absorption coefficient. , However, there are few examples of coordination-based coumarin fluorescent probes for detecting palladium­(II) ions. , Under this background, we begin to evaluate the sensing performance of an easily prepared coumarin Schiff base containing a thioether recognition fragment (compound CBBS ) for palladium­(II) ions. Furthermore, revealing the spectral properties of a coumarin-based fluorescence molecule with a thioether fragment could guide the design of the other coordination-based fluorescence probes for sensing metal ions.…”
Section: Introductionmentioning
confidence: 99%